Au-delà de la catégorie « césarienne sur demande maternelle ». Cultures médicales et expériences de mères en Suisse romande - Irene Maffi (Anthropologie & Santé)
In this article, I examine the socio-cultural and biomedical logics underlying maternal requests for caesarean sections, and analyse the multiplicity of women’s motivations. I aim to add complexity to the medical category of “maternal request”, which presupposes an abstract subject with the capacity to make autonomous choices regardless of the socio-cultural and technological context. The purpose is to explore how maternal demand for a caesarean section arises within new social and biomedical norms relating to birth, femininity and motherhood. Analysing the accounts of four mothers I met during ethnographic research in French-speaking Switzerland, I examine their personal motivations and how they fit into specific biomedical systems and social and gender norms. I focus on class, level of education and national origin as important factors, both in the relationship with health professionals and in the approach to the female body and childbirth.